Making homes ethnography and design - Pink, Sarah 1966-; Mackley, Kerstin Leder ca. 20. Jh; Moroşanu, Roxana ca. 20. Jh; Mitchell, Val ca. 20. Jh; Bhamra, Tracy ca. 20. Jh (Bloomsbury Academic, 2017)
"Making Homes: Anthropology and Design is a strong addition to the emerging field of design anthropology. Based on the latest scholarship and practice in the social sciences as well as design, this interdisciplinary text introduces a new design ethnography which offers unique and original approaches to research and intervention in the home. Presenting a coherent theoretical and methodological framework for both ethnographers and designers, the authors examine 'hot' topics - ranging from movements and mobilities to im/material environments, to digital culture - and confront the challenges of a research and design environment which seeks to bring about the changes required for a sustainable, resilient, 'safe', and comfortable future. Written by leading experts in the field, the book draws on real-life examples from a wide range of international projects developed by the authors, other researchers, and designers. Illustrations throughout help to convey the methods and research visually. Readers will also have access to a related website which follows the authors' ongoing research and includes video and written narrative examples of ethnographic research in the home. Transforming current understandings of the home, this is an essential read for students and researchers in fields such as design, anthropology, human geography, sociology, and media and communication studies"--
Keywords: Gesellschaft; Design; Wohnen; Wohnung; Ethnologie; Dwellings / Social aspects; Dwellings / Design and construction; Design / Anthropological aspects; SOCIAL SCIENCE / Anthropology / General; DESIGN / History & Criticism; SOCIAL SCIENCE / Research; Aufsatzsammlung